Clinical Complications of Iron Overload in Patients with Myelodysplastic Syndromes: a literature review - Carvalho, Luiz Gustavo; de Morais Batista, Andressa Hellen; Cerqueira Sousa, Isabelle (Brazilian Journal of Case Reports, 2021)
Myelodysplastic Syndromes (MDS) are a group of heterogeneous hematologic disorders characterized by bone marrow involvement. Iron overload is the result of multiple transfusions and high levels of apoptosis. Based on a literature review, ferritin was identified as an important marker of iron accumulation in organs such as liver, heart and pancreas in patients with MDS. Some studies also demonstrated that iron overload caused cell cycle arrest causing apoptosis and progression to leukemia, high levels of reactive oxygen species and low levels of HIF-1a, causing apoptosis, being related to the presence of cytopenia in MDS.